IMPLEMENTASI TANGGUNG JAWAB PELAKU USAHA TERHADAP PENJUALAN SEPATU BERMEREK PALSU DI KECAMATAN TAMPAN KOTA PEKANBARU - Desi Muzdalifah; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In addition to copyright and patents, trademark rights has also become a part of the intellectual property rights that must be protected from the legal aspect. Not Maximum efforts are made to reduce violations of the brand led to the present distribution of the goods of violations still occur. Traders itself has continued to trade in fake goods by using well-known brands such as Nike, Adidas, Bilabong, Ripcurl, channel and much more.In the world of trade, the brand as one form of intellectual property has an important role has been used to distinguish the origin of goods and services. A brand becomes a valuable asset because it make the price of a product expensive.Sales of fake designer goods is licensee of the mark concerned may sue the other party who intentionally use the brand to earn greater profits by using the brand without permission owner of the mark.The research method is that the yuridict sociological law research and data collection is done by searching for information based on the questionnaires, interview and review of literature which it aims.Keywords : famous brands, counterfeit brands, consumer protection.